Rumen Protected Choline along with Green Tea Extract maintain Glucose Homeostasis in Transition Karan Fries Cows - Acharya, Parag; Lathwal, S S; Patnaik, Neela Madhav; Moharana, Baisakhi (Indian Journal of Animal Nutrition, 2019)
The present study has been aimed to explore the effect of supplementation of rumen protected choline (RPC) and green tea extract (GTE) on glucose homeostasis in transition cows. The present experiment was carried out on thirty-two pregnant Karan Fries (KF) cows. In control group, cows were fed basal diet. In T1 each cow was fed rumen protected choline (RPC) (55g/day), in T2 - green tea extract (GTE) (3g/d) and in T3- RPC + GTE (55+3) g/day along with basal diet. The duration of experiment was 30 days before calving to 60 days after parturition. No significant (p ≥ 0.05) difference was observed across the groups for plasma glucose concentration. The concentration of insulin and IGF-1 increased significantly (p≤ 0.01) in T1, T2 and T3 as compared to control in days’ dependant manner around parturition. In conclusion, feeding of RPC and GTE in combination maintained glucose homeostasis during transition period in Karan Fries cows.